ANALISIS LAJU PEMBANGUNAN MANUSIA DI PROVINSI PAPUA TAHUN 2015-2017 - Rafly Parenta Bano Parenta Bano (SOCIETAS, 2019)
Until 2017, Papua was the only province in Indonesia where human development was classified aslow at 59.09. However, the speed of human development in the last three years is the highest in Indonesia. The purpose of this study is to determine the speed of human development in Papua during 2015-2017 and comparison with other provinces in Indonesia and predict how many years it will take so that human development in Papua can be equal to that of other provinces. Although this study only uses a very simple descriptive analysis method, but by applying the velocity formula of two moving objects it can produce important information to develop strategies to boost human development in Papua. As a result, President Jokowi's development policy in Papua made the speed of human development in Papua Province ranked first (top movers) during 2015-2017 with its an average annual speed is 1.36 percent per year. This achievement is higher than the achievements of West Papua and Maluku Provinces. It means that assuming a human development situation such as this period, within the next 15 years, human development achievements in the Papua Province will be able to outperform human development in West Papua and Maluku Provinces.